2013
DOI: 10.1002/ejsp.1956
|View full text |Cite
|
Sign up to set email alerts
|

Unwilling, but not unaffected—Imagined contact effects for authoritarians and social dominators

Abstract: According to a dual process model perspective, intergroup contact should be particularly effective for people high in right-wing authoritarianism (RWA), but not for those high in social dominance orientation (SDO), because of different underlying motivational goals. In the present studies, we tested the hypothesis that imagined contact, that is, the mental representation of a positive intergroup encounter, improves intergroup relations for high RWAs. In two experimental studies, we showed that high RWAs, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 47 publications
7
57
0
1
Order By: Relevance
“…Husnu and colleagues first demonstrated this effect in the context of prolonged conflicts in Cyprus (Crisp, Husnu, Meleady, Stathi, & Turner, 2010;. Turkish Cypriot and Greek Cypriot participants who imagined having contact with members of the opposite group subsequently expressed greater intentions to positively engage with previously stigmatized groups in the future (see also Asbrock, Gutenbrunner, & Wagner, 2013;Birtel & Crisp, 2012a;Stathi, Crisp, & Hogg, 2011;Vezzali, Stathi, Crisp, & Capozza, 2015). In a similar vein, imagined contact has been shown to change approach and avoidance behavioral tendencies.…”
Section: The Behavioral Consequences Of Imagined Contactmentioning
confidence: 95%
“…Husnu and colleagues first demonstrated this effect in the context of prolonged conflicts in Cyprus (Crisp, Husnu, Meleady, Stathi, & Turner, 2010;. Turkish Cypriot and Greek Cypriot participants who imagined having contact with members of the opposite group subsequently expressed greater intentions to positively engage with previously stigmatized groups in the future (see also Asbrock, Gutenbrunner, & Wagner, 2013;Birtel & Crisp, 2012a;Stathi, Crisp, & Hogg, 2011;Vezzali, Stathi, Crisp, & Capozza, 2015). In a similar vein, imagined contact has been shown to change approach and avoidance behavioral tendencies.…”
Section: The Behavioral Consequences Of Imagined Contactmentioning
confidence: 95%
“…Voci et al (2015) suggested that high ingroup identifiers are prone to show stronger contact effects since they initially hold more extreme attitudes and contact effects may generalize more strongly and easily for high ingroup identifiers for whom group membership is a salient aspect of intergroup relations (e.g., Brown & Hewstone, 2005). Studies in imagined contact literature have also confirmed this by demonstrating imagined intergroup contact to be more effective among high right-wing authoritarians (Asbrock et al, 2013) and the ones who had lower levels of previous direct contact (Hoffarth & Hodson, 2016) and higher levels of initial prejudice (West, Hotchin, & Wood, 2017). Therefore, we argued that Turkish participants with higher levels of ethnic ingroup identification would show greater contact effects and benefit more from imagined contact.…”
Section: S Tu D Ymentioning
confidence: 95%
“…Despite these encouraging findings, the imagined contact field still faces challenges: some have been unable to replicate the imagined contact effects [48][49][50][51]; others have found limited effects of imagined contact among minority group members [52]; it is not clear how long the effects last for adults or how imagined contact is most effectively combined with other forms of contact; and, as with other contact interventions [23*], effect sizes are typically small.…”
Section: Imagined Contactmentioning
confidence: 99%